Pengaruh Sikap Keuangan, Pengetahuan Keuangan, Efikasi Diri Keuangan Terhadap Perilaku Manajemen Keuangan Melalui Pengendalian Diri Sebagai Variabel Intervening (Studi Pada Pelaku UMKM Ekonomi Kreatif Sub Sektor Fashion di Kota Malang pada tahun 2021) - Siti Maghfirotul Ummah; Jeni Susyanti; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThe creative economy sector is a sector that have the most impact due to in Covid-19 pandemic, namely msmes. Several factors limit msmes in Indonesia, one of which is that people must use the income they earn. It affects financial decisions that are useful in everyday life. Many factors can be obstacles faced by msmes in Indonesia. The purpose of this study was to determine the financial management bevahior of msme actors. This research uses a quantitative approach method with non-probability sampling method. The population used is 150. The data analysis method uses the smartpls program by testing the validity and reliability of the construct, outer model and inner model. The results of the study concluded that financial attitudes had a significant and positive direct effect on locus of control. Pengetahuan Keuangan and financial self-efficacy have an insignificant and direct positive effect on locus of control. Financial attitudes have a significant and direct positive effect on financial management bevahior. Financial knowledge, financial self-efficacy and locus of control have an insignificant and direct positive effect on financial management bevahior. Locus of control is not able to mediate the influence of financial attitudes, financial knowledge and financial self-efficacy on financial management bevahior in fashion sub-sector smes in Malang in 2021.Keywords: Financial Self Efficacy, Locus Of Control, Financial Management Bevahior